If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 3 + m + 1 = 0 Reorder the terms: 3 + 1 + 4m + m = 0 Combine like terms: 3 + 1 = 4 4 + 4m + m = 0 Combine like terms: 4m + m = 5m 4 + 5m = 0 Solving 4 + 5m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 5m = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 5m = 0 + -4 5m = 0 + -4 Combine like terms: 0 + -4 = -4 5m = -4 Divide each side by '5'. m = -0.8 Simplifying m = -0.8
| 6(2y+3)-4(y-5)=0 | | 4x+4y+4z+4= | | 2x+10=64 | | 3c+4d+5c+8= | | 3a+2+3a+7= | | 2(4+3r)=3(r+1)+11 | | 5x=x+10 | | 4(2y+5)=3(5y-2) | | 8+2x-3=25 | | 4a-6-2(a-1)= | | 5a-2-3a+7= | | -2a+3a+6= | | 6q-9=12+3q | | -3(m-1)+4m+2= | | 4=x^2-7 | | 7x+4-5x-8= | | 5x-4=2(x-2) | | 2x+16y+13=0 | | 22y+8=23y-4 | | 5x^2+500=844.45 | | 6x+2x+3= | | 7*x^2+84=0 | | 2(3+7x)-(1+15x)=2 | | y=1-8x | | -4p-6q-5= | | x=3y-4 | | 3a+5b+4+6a= | | (4x+51)= | | 2x+3x+4+4x= | | 6y+13+5y+2=180 | | -4x-7=3(2-x) | | -21x-29x=-56 |